Perceived Driving Difficulty, Negative Affect, and Emotion Dysregulation in Self-Identified Autistic Emerging Drivers - Fok, Megan; Owens, Justin M.; Ollendick, Thomas H.; Scarpa, Angela (Frontiers in Psychology, 2022)
Driving is central to adult independence and autonomy; yet most autistic young adults do not acquire driver’s licenses. It is important to understand barriers to achieving this milestone for autistic adults. Differences in negative affect and emotion dysregulation associated with autism may interfere with managing difficult driving situations. The current study compared perceived DD, emotion dysregulation, and negative affect in emerging drivers with and without autistic traits (AT), and investigated how emotion dysregulation and negative affect relate to perceived DD. We expected 1) greater perceived DD, emotion dysregulation, and negative affect in participants with AT, and 2) a positive correlation of perceived DD with both emotion dysregulation and negative affect in the whole sample. Thirty-seven adolescents and young adults (15 AT) self-reported perceived DD in 15 scenarios and completed the Difficulty in Emotion Dysregulation Scale (DERS) and the Depression, Anxiety, and Stress Scale (DASS). Autistic participants scored significantly higher on mean perceived DD, DERS Impulse subscale, DASS total and DASS Stress subscale scores. Perceived DD positively correlated with the DERS and DASS total scores, all DASS subscales, and DERS Nonacceptance, Goals, and Impulse subscales across the whole sample. The findings highlight the roles of emotion dysregulation and negative affect in perceived DD in emerging drivers with AT. In particular, emotional stress and impulsivity may map onto mechanisms of over-reactivity to negative affect and explain why autistic people perceive particular situations as difficult when driving. Implications and directions for future research are discussed.